1988
DOI: 10.1095/biolreprod39.3.519
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Relaxin on Cyclic Adenosine 3′, 5′-Monophosphate Concentrations in Human Endometrial Glandular Epithelial Cells1

Abstract: The effects of relaxin (RLX), forskolin (Fk), and 4-(3-butoxy-4-methoxybenzyl)-2-imidazolidinone (Ro, a phophodeisterase inhibitor) on the accumulation of cyclic adenosine 3',5'-monophosphate (cAMP) in human endometrial glandular epithelial cells were studied. Epithelial glands were isolated from the endometrium by digesting the viable tissue fragments with collagenase. The epithelial glands were incubated with Ro, RLX, and Fk separately or in combination. The amount of cAMP was determined at the end of incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 0 publications
3
23
0
Order By: Relevance
“…Results from various studies provide abundant evidence that relaxin is a potent regulator of the differentiated function of human endometrial cells in vitro (14,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Relaxin stimulates the production of prolactin (16,17,19), insulin-like growth factor (18), and insulin-like growth factor binding protein 1 (IGFBP-1) (19), in progestin-primed endometrial stromal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from various studies provide abundant evidence that relaxin is a potent regulator of the differentiated function of human endometrial cells in vitro (14,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Relaxin stimulates the production of prolactin (16,17,19), insulin-like growth factor (18), and insulin-like growth factor binding protein 1 (IGFBP-1) (19), in progestin-primed endometrial stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…A role for relaxin in human endometrial function is also supported by findings that relaxin binds specifically and with high affinity to human endometrial cells (15). In addition, a large body of evidence exists to demonstrate that relaxin has definitive effects on human endometrial cells in vitro (14,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Relaxin stimulates production of several endometrial products including prolactin, glycodelin, insulin-like growth factor binding protein 1 (IGFBP-1) and vascular endothelial growth factor in progestin-primed human endometrial cells in vitro.…”
mentioning
confidence: 99%
“…Interestingly, this intracellular signalling pathway has been implicated as a second messenger for relaxin in other systems (58)(59)(60). Since both IGF-I and insulin block both the relaxin-and cAMP-induced stimulation of decidual IGF-BP-I synthesis, it is possible that cAMP may be mediating the relaxin signal.…”
Section: Discussionmentioning
confidence: 99%
“…4). Early studies before receptor identification, showed that treatment with relaxin increased cAMP accumulation in THP-1 cells (Parsell et al, 1996), MCF-7 cells (Bigazzi et al, 1992), the mouse pubic symphysis (Braddon, 1978), uterine strips (Sanborn et al, Relaxin Family Peptide Receptors 1980), uterine longitudinal muscle (Osa et al, 1991) from estrogen-primed rats, and in cultures of human endometrial cells (Fei et al, 1990), human endometrial glandular epithelial cells (Chen et al, 1988), newborn rhesus monkey uterine cells (Kramer et al, 1990), rat myometrial cells (Hsu et al, 1985), and rat anterior pituitary cells (Cronin et al, 1987). The importance of cAMP as a signaling pathway for relaxin was confirmed on RXFP1 deorphanization, because constitutively active mutants of RXFP1 (TM6: D637Y) increased cAMP accumulation in a ligandindependent manner (Hsu et al, 2000.…”
Section: Signal Transduction Pathwaysmentioning
confidence: 99%
“…Interaction of relaxin with RXFP1 to trigger cell signaling involves at least three stages: high-affinity binding between the B-chain of relaxin and the RXFP1 LRR region, lower affinity binding to the TM extracellular loops (ECLs), and finally an essential interaction involving the LDLa module (Sudo et al, 2003;Halls et al, 2005b). Although RXFP1 couples to numerous signal transduction pathways, many early studies in reproductive tissues indicated that relaxin caused increases in cAMP levels (Braddon, 1978;Cheah and Sherwood, 1980;Sanborn et al, 1980;Chen et al, 1988), and a constitutively active receptor mutant also generates cAMP . The pattern of cAMP production after stimulation of HEK293 cells expressing RXFP1 is complex and involves at least three G proteins (Halls et al, 2006(Halls et al, , 2009a.…”
Section: Introductionmentioning
confidence: 99%